11/2 x 2 +x = 1/7 Tìm x nha
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
3-/x-5/=-7+/-8/
3-/x-5/=-7+8
3-/x-5/=1
/x-5/=3-1
/x-5/=2
=>x-5=2 hoặc x-5=-2
x=5+2 x=5+(-2)
x=7 x=3
vậy x\(\in\){3;7}
\(1.\)\(3-\left|X-5\right|=-7+\left|-8\right|\)
\(3-\left|X-5\right|=-7+8\)
\(3-\left|X-5\right|=1\)
\(\left|X-5\right|=3-1\)
\(\left|X-5\right|=2\)
\(\Rightarrow X-5=2\)\(ho\text{ặ}c\)\(X-5=\left(-2\right)\)
\(N\text{ếu}\)\(X-5=2\) \(N\text{ếu}\)\(X-5=\left(-2\right)\)
\(X=5+2\) \(X=\left(-2\right)+5\)
\(X=7\) \(X=3\)
x:8/11=11/3
x=11/3X8/11
x=8/3
b) 2/5:x=1/4
x=2/5:1/4
x=8/5
c)4/5+5/7:x=1/6=?
ai tích mình tích lại
Tìm x . biết :
\(a,\frac{2}{5}:\left(-x-\frac{1}{2}\right)=\frac{4}{5}\)
\(\Rightarrow-x-\frac{1}{2}=\frac{2}{5}:\frac{4}{5}\)
\(\Rightarrow-x-\frac{1}{2}=\frac{2}{5}.\frac{5}{4}\)
\(\Rightarrow-x-\frac{1}{2}=\frac{1}{2}\)
\(\Rightarrow-x=\frac{1}{2}+\frac{1}{2}\)
\(\Rightarrow-x=1\)
\(\Rightarrow x=-1\)
Vậy \(x=-1\)
a. \(\frac{2}{5}.\left(-x-\frac{1}{2}\right)=\frac{4}{5}\)
\(\Rightarrow-x-\frac{1}{2}=\frac{2}{5}:\frac{4}{5}\)
\(\Rightarrow-x-\frac{1}{2}=\frac{2}{5}.\frac{5}{4}\)
\(\Rightarrow-x-\frac{1}{2}=\frac{1}{2}\)
\(\Rightarrow-x=\frac{1}{2}+\frac{1}{2}\)
\(\Rightarrow-x=1\)
\(\Rightarrow x=-1\)
\(\dfrac{\dfrac{22}{15}}{11-x}\) + \(\dfrac{2}{3}\) = \(\dfrac{7}{5}\)
\(\dfrac{\dfrac{22}{15}}{11-x}\) = \(\dfrac{7}{5}\) - \(\dfrac{2}{3}\)
\(\dfrac{\dfrac{22}{15}}{11-x}\) = \(\dfrac{11}{15}\)
11 - \(x\) = \(\dfrac{22}{15}\) : \(\dfrac{11}{15}\)
11 - \(x\) = 2
\(x\) = 11 - 2
\(x\) = 9
\(\frac{-5}{7}.\frac{2}{11}+\frac{-5}{7}.\frac{9}{11}\) \(\frac{3}{5}.\frac{2}{8}+\frac{-6}{16}.\frac{2}{5}+\frac{-6}{15}:\left(-16\right)\)
\(=\frac{-5}{7}\left(\frac{2}{11}+\frac{9}{11}\right)\) \(=\frac{3}{20}+\frac{-3}{20}+\frac{1}{40}\)
\(=\frac{-5}{7}.1=\frac{-5}{7}\) \(=0+\frac{1}{40}=\frac{1}{40}\)
\(x-\frac{2}{5}=0,24\) \(\left(\frac{7}{3}x-0,6\right):3\frac{2}{5}=1\)
\(\Rightarrow x=0,24+\frac{2}{5}=\frac{16}{25}\) \(\Rightarrow\left(\frac{7}{3}x-0,6\right):\frac{17}{5}=1\)
vậy x = 16/25 \(\Rightarrow\frac{7}{3}x-0,6=\frac{17}{5}\)
\(\Rightarrow\frac{7}{3}x=\frac{17}{5}+0,6=4\)
\(\Rightarrow x=4:\frac{7}{3}=\frac{12}{7}\)
vậy x = 12/7
( 15 - x ) + ( x - 12 ) = ( -5 + x )
( 15 - 12 ) - x + x = -5 + x
3 = -5 + x
x = 3 + 5
x = 8
(x+1)+(x+3)+(x+5)+...+(x+99)=0
( x + x + x + .... + x ) + ( 1 + 3 + 5 + ... + 99 ) = 0
50x + 2500 = 0
50x = -2500
x = -2500 : 50
x = -50
bài 2
a) 2448:[119-(x-6)]=24
119-(x-6)=2448:24
119-(x-6)=102
x-6=119-102
x-6=17
x=17+6
x=23
\(\dfrac{11}{2}\cdot2+x=\dfrac{1}{7}\\ 11+x=\dfrac{1}{7}\\ x=\dfrac{1}{7}-11\\ x=\dfrac{1}{7}-\dfrac{77}{7}\\ x=\dfrac{-76}{77}\)
\(\dfrac{11}{2}.2+x=\dfrac{1}{7}\)
\(11+x=\dfrac{1}{7}\)
\(x=\dfrac{1}{7}-11\)
\(x=-10\dfrac{6}{7}\)